Modelagem numérica da flexão de vigas de concreto reciclado armado - Mota, Magno Teixeira (2013)
The economic development and population growth cause the intense use of nonrenewable natural resources, causing the increasing in waste generation, such as the construction and demolition waste (CDW). The use of recycled aggregates from CDW in the production of concrete is one alternative to reducing the environmental problems caused by these waste. Several studies have shown that, in general, these aggregates cause changes in important engineering properties, such reduction of the compressive strength and modulus of elasticity. Nevertheless, some researches indicate the possibility of their use in the production of structural elements with satisfactory mechanical performance. In order to contribute to the safe prediction of the behavior of structural concrete made with recycled aggregates from CDW, in this work was carried out numerical modeling of the bending of reinforced recycled concrete beams, using the DIANA© software. The numerical results indicate that, in general, it is possible to predict satisfactorily the flexural behavior of reinforced recycled concrete beams